Modeling and Parametric Investigation of Rotating Packed Bed Processes for CO2 Capture and Mineralisation - Marianthi Dimoliani (AIDIC Servizi S.r.l., 2021)
Rotating Packed Beds (RPB) are receiving increased attention in CO2 capture, due to their considerably lower volume compared to conventional packed-beds and their beneficial effects on process capital costs. As a result of these advantages, RPB have also been considered as a CO2 mineralisation option for the production of precipitated calcium carbonate (PCC). In the area of CO2 capture, the few model-based investigations employ either the two-film or Higbie’s penetration theory to model the gas-liquid mass transfer as the main driving force of the systems’ operation. In the area of PCC production, there is only one model type available that is based on the two-film theory. While the latter includes the limiting assumption of linear and steady-state mass transfer within the liquid film, Higbie’s theory is considerably closer to realistic operation due to the assumption of time-dependent and non-linear, gas-to-liquid mass transfer. Considering this significant advantage, this work proposes for the first time a model for RPB-based, PCC production using Higbie’s penetration theory. The model is first developed and validated considering solvent-based CO2 capture with monoethanolamine (MEA) solvent, taking advantage of the available experimental data in published literature. The model is then adapted to PCC production to perform a parametric investigation based on various performance indicators. Results indicate that the proposed model enables improved accuracy compared to the two film theory. Higher rotation speeds and liquid flowrates enable improved mass transfer, whereas PCC production can be achieved at lower energy consumption simultaneously with high CO2 capture efficiency.